1999
DOI: 10.1037/h0089989
|View full text |Cite
|
Sign up to set email alerts
|

Families and the genetic revolution: Implications for primary healthcare, education, and research.

Abstract: This article provides an overview of the Human Genome Project (HGP) and its outcomes in science, health, and healthcare practices and education for health professionals. An analysis of findings from the HGP for familial hypertrophic cardiomyopathy (FHCM) and breast cancer are used as a framework for examining unique issues of families responding to genetic discoveries. The paucity of attention to family systems and family relationships in the collection and dissemination of genetic information places family me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Case descriptions have indicated that a hereditary disease has a profound impact on the balance of the relationship with the partner or family (Demyttenaere, Evers‐Kiebooms, & Decruyenaere, 1992; DudokdeWit, et al, 1996; DudokdeWit, Meijers‐Heijboer, Tibben, et al, 1994; DudokdeWit, Tibben, Frets, Meijers‐Heijboer, et al, 1997; Hayes, 1992; Huggins et al, 1992; Marteau & Richards, 1996). As Sobel and Cowan state in their qualitative study, genetic testing is a family, as opposed to an individual matter (Sobel and Cowan, 2000), but more research is needed to narrow the gap between offering the predictive test and understanding its impact on the wider scale of family functioning (Feetham, 1999; Peters, Djurdjinovic, & Baker, 1999; Rolland, 1999; Taswell, & Sholtes, 1999).…”
Section: Questions Raisedmentioning
confidence: 99%
“…Case descriptions have indicated that a hereditary disease has a profound impact on the balance of the relationship with the partner or family (Demyttenaere, Evers‐Kiebooms, & Decruyenaere, 1992; DudokdeWit, et al, 1996; DudokdeWit, Meijers‐Heijboer, Tibben, et al, 1994; DudokdeWit, Tibben, Frets, Meijers‐Heijboer, et al, 1997; Hayes, 1992; Huggins et al, 1992; Marteau & Richards, 1996). As Sobel and Cowan state in their qualitative study, genetic testing is a family, as opposed to an individual matter (Sobel and Cowan, 2000), but more research is needed to narrow the gap between offering the predictive test and understanding its impact on the wider scale of family functioning (Feetham, 1999; Peters, Djurdjinovic, & Baker, 1999; Rolland, 1999; Taswell, & Sholtes, 1999).…”
Section: Questions Raisedmentioning
confidence: 99%
“…Genetic testing is increasingly being recognized as both a family and an individual experience. There is growing recognition among clinicians and researchers that families influence and are influenced by how individual family members make sense of, respond to, and use the information they receive during the genetic testing experience 1–10 . The decision to undergo genetic testing is anchored in the individual's explanatory model or beliefs about the onset, cause, predictability, seriousness, course, and treatment of the genetic condition being tested for 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The phenomena of concern for nurses relevant to genetics and health care have been described by the International Society of Nurses in Genetics and American Nurses Association (1998) and are listed in Table 3. Other areas of concern include: decision making, family functioning; stress, coping and adaptation; uncertainty and ambiguity; stigmatization and discrimination; values, beliefs, spirituality and religiosity (Feetham, 1999). The information depicted in Figure 1 enables the nurse to plan and provide holistic care for patients and families with due consideration for these phenomena.…”
Section: Introductionmentioning
confidence: 99%